Adsorption Studies on Activated Charcoal Prepared from Agricultural Wastes - Deshmukh, M.R.; Arbale, V.A.; Belhekar, A.A.; Kashalkar, R.V.; Deshpande, N.R. (Asian Journal of Chemistry, 2010)
Activated charcoals have been prepared from the agricultural wastes of Cajans cajan and Cicer arietinum using chemical activating agents such as ZnCl2 and orthophosphoric acid. Adsorption studies on the carbon samples TCzn, TCph and HCzn obtained from Cajanus cajan and Cicer arietinurn have shown that all the materials have a good uptake capacity for acetic acid and oxalic acid. Langmuir adsorption isotherm is valid for all the carbon samples. Preliminary studies of adsorption of p-chlorophenol on all carbon samples have also given encouraging results. TCzn = Charcoal from Cajanus cajan activated with 10% ZnCl2 TCph = Charcoal from Cicer arietinum activated with 20% phosphoric acid HCzn = Charcoal from Cicer arietinum activated with 10% ZnCl2